2015
DOI: 10.1016/j.envres.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of perfluoroalkyl substances from mother to fetus in a Spanish birth cohort

Abstract: Our results suggest that PFAS fetal body burden can be assessed using as proxy maternal plasma or serum collected early in pregnancy. Maternal age might influence PFAS placental transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 45 publications
14
80
4
Order By: Relevance
“…concentrations support previous measurements from pregnant women (Monroy et al, 2008;Okada et al, 2013Okada et al, , 2014Cho et al, 2015;Manzano-Salgado et al, 2015;Papadopoulou et al, 2015;Callan et al, 2016;Wang et al, 2016). PFUnDA has been previously detected both at higher and lower concentrations (Okada et al, 2013;Callan et al, 2016;Wang et al, 2016).…”
Section: Pfassupporting
confidence: 89%
See 1 more Smart Citation
“…concentrations support previous measurements from pregnant women (Monroy et al, 2008;Okada et al, 2013Okada et al, , 2014Cho et al, 2015;Manzano-Salgado et al, 2015;Papadopoulou et al, 2015;Callan et al, 2016;Wang et al, 2016). PFUnDA has been previously detected both at higher and lower concentrations (Okada et al, 2013;Callan et al, 2016;Wang et al, 2016).…”
Section: Pfassupporting
confidence: 89%
“…The differences in foetal uptake may be due to differences in placental clearance or exposure duration. Previously, foetal concentrations of PFOS, PFOA, and PFNA have been estimated from the concentrations in the umbilical cord blood (Monroy et al, 2008;de Cock et al, 2014;Manzano-Salgado et al, 2015). Our results help qualify estimations of foetal exposure by providing actual measured concentrations.…”
Section: Pfass In Human Foetal Organs In Relation To Maternal Concentsupporting
confidence: 55%
“…1. The median PFHxS level of cord serum in this study (3.87 ng/mL) is much higher than those found in most reported findings, such as South Africa (0.3 ng/mL) (Hanssen et al 2010), Spain (0.4 ng/mL) (Manzano-Salgado et al 2015), Korea (0.57 ng/mL in 2011) , and China (0.06 ng/mL) (Liu et al 2011). However, consistent with our results, an investigation from the Faroe Islands (Needham et al 2011) collected 15 sets of maternal and cord blood, and milk in 2000, showing that PFHxS levels in cord serum (9.1 ng/mL) were higher than PFOS (6.6 ng/mL) or PFOA (3.1 ng/mL).…”
Section: The Pfass Concentration In Cord Serumcontrasting
confidence: 73%
“…It is known that the type of functional group and the carbon length could affect the transplacental transfer efficiency. For example, shorter chain PFASs are transferred more easily than long chain (Beesoon et al 2011;Manzano-Salgado et al 2015;Monroy et al 2008). In the study from Needham et al (2011), the higher ratio of transplacental transfer in PFHxS (median ratio of 0.74) than PFOA (median ratio of 0.72) and PFOS (median ratio of 0.34) was observed.…”
Section: The Pfass Concentration In Cord Serummentioning
confidence: 98%
“…There is evidence that PFASs accumulate in fetal tissue with different efficiencies, and differential transfer of compounds from maternal plasma to fetal tissue may explain our findings (3537). A study of Danish women found that of 5 PFASs analyzed (PFOS, PFOA, PFNA, PFDA, PFUnDA), PFDA and PFUnDA had the highest concentrations in both placenta and fetal tissues relative to maternal concentrations (36).…”
Section: Discussionmentioning
confidence: 69%